Exploring wireless device-free localization technique to assist home-based neuro-rehabilitation - Wang, Zhen; Li, Xiaoou; Wang, Guoli (Frontiers in Neuroscience, 2024)
Home-based movement neuro-rehabilitation is quite necessary when the patient goes back home from hospital. Due to lack of supervision from doctors, rehabilitation at home is often forgotten. As an alternate to doctor-supervision, in this research, we explore the wireless devicefree localisation technique to assist the rehabilitation procedure. The localisation technique can judge whether the patient is near the rehabilitation equipment and even obtain the movement trajectory. The most challenging problem in the wireless device-free localisation system is that the received-signal-strength (RSS) of the electromagnetic-wave is unpredictable, which increases the localisation error. How to select the informative RSS is pretty important. This research proposes a new criterion (i.e. fluctuation-level) to select the informative RSS. Experimental results show the effectiveness of the proposed fluctuation-level in reducing the localisation error.